Kebudayaan Sebagai Suatu Komitmen Kesadaran Diri untuk Mengangkat Tradisi sebagai Konsep Contemporary Vernacular pada Interior dan Arsitektur - Doni Morika (Humaniora, 2011)
Humans are part of the natural environment or, in the context of human culture to use reason and mind to be able to coexist with nature. But the more advanced capabilities of human thought and the further development of technologies that make, the pattern of human origin in order to live in harmony with nature the more degenerate into an attempt to conquer nature. Associated with the times, 'needs' and 'demand' from the user will be higher, both in terms of function and aesthetics. A design must be able to also follow the movement pattern of the trend that occurred in the community to be recognized. Through discourse Contemporary Vernacular Architecture in the Interior and revealed in some design work, as object of study is the existence of a work done by several designers and architects in Indonesia as a commitment to self-awareness to lift a tradition contained in Sundanese culture.